PPP time and frequency transfer independent of time-varying receiver biases - El-Mowafy, Ahmed (2023)
Precise point positioning (PPP) has become a competitive time and frequency transfer technique using global navigation satellite system (GNSS) measurements. The core objective of PPP time and frequency transfer is to obtain high-precision solutions for the receiver clock parameter. However, due to the linear correlation between the receiver clock, code biases and phase biases in the PPP model, those three types of parameters cannot be estimated separately. When constructing the full-rank PPP model, the receiver clock parameter absorbs the ionosphere-free (IF) receiver code bias and thus loses its original form. In traditional PPP time and frequency transfer, it is usually assumed that the receiver code biases are time-invariant, which is not always true. Studies have shown that receiver code biases may have significant time variability, which inevitably affects the time and frequency transfer performance. Therefore, in this contribution, the receiver code biases are considered time-variant parameters in the filtering process. They are made estimable by choosing the first-epoch receiver code biases as the datum. The IF PPP and uncombined (UC) PPP considering time-varying receiver biases will be considered. In this sense, only the IF receiver code bias of the first epoch will be included in the estimable receiver clock so that the time and frequency transfer will no longer be affected by time-varying receiver biases. The time-varying behaviors of the receiver code biases will first be shown, which will show that the time-invariant assumption of the IF receiver bias is not always reasonable. Next, the time and frequency transfer performance of PPP considering the time-varying receiver biases will be compared with traditional PPP approach. Improvements in time transfer and long-term frequency stability of PPP considering time-varying receiver code will be demonstrated.